Commercial Dairy Farmers Preference towards Livestock Extension Services in Karnataka - Sathisha M.C., Rupasi Tiwari; Rakesh Roy (Indian Journal of Extension Education, 2018)
Karnataka has been purposively selected due to the leading producer of milk and commercial dairy farming is in developing stage as compared to other states of South India. Three districts namely Kolar, Chikkaballapura and Ramnagar were selected purposively due to its highest milk production. In all, 135 respondents form the total sample size for the study having equal representation of small (10-20 milch animals), medium (20-40 milch animals) and large (>40 milch animals) commercial dairy farmers. The study reveals that respondents mostly accessed breeding and livestock healthcare services from veterinarians followed by paravets and KMF doctors whereas feeding services from milk cooperatives followed by self-prepared and KMF doctors. The study also revealed that respondents mostly accessed marketing service from milk cooperatives followed by milk vendors and self-marketing. For acquiring information, respondents mostly accessed veterinarians followed by dairy cooperatives and paravets. Among personal cosmopolite sources dairy farmers mostly accessed television followed by internet and radio while among personal localite sources they mostly accessed neighbour followed by friend and progressive farmer. The study also reveals that respondents mostly accessed insurance services from government agencies followed by private agencies and veterinary and animal husbandry department. The study further shows that majority of the large commercial dairy farmers never insured their animal as they felt insurance as a financial burden for them.